Establishment of non-methyl eugenol-attracted males of oriental fruit fly, Bactrocera dorsalis (Hendel) supplemented with semiochemicals - Mandanayake, Mandanayake Arachchilage Ruwanthi Anuradha (2021)
The Oriental fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae), is one of the world’s most destructive and invasive pest of fruits. Control of this insect has relied heavily on the Male Annihilation Technique (MAT), and the Sterile Insect Technique (SIT). Combined use of MAT and SIT offers excellent control of B. dorsalis. However, issues with sterile males getting killed by going to those MAT traps have reduced the efficacy of both techniques. Nonetheless, the availability of non-ME-responding male B. dorsalis would enable the simultaneous application of MAT and SIT. The objectives of this study were to establish domesticated B. dorsalis lines and screen them for non-attraction to methyl eugenol (ME), to ascertain further those non-ME-attraction phenotypic expression, to evaluate the attraction of any non-ME-responding (NR) males to semiochemicals such as zingerone (ZN) and β–caryophyllene (BCP), and to evaluate the effects of consuming those semiochemicals by males on their mating success. Thus, as a part of a laboratory-scale proof of concept, the possibility of raising NR males of B. dorsalis that were supplemented with exposure to those compounds for enhanced mating advantage against wild males was explored. First, domesticated lines of B. dorsalis colonies reared from larvae in infested Syzygium sp. fruits were established and those males screened for non-ME responsiveness. Flies were collected from four different locations and those males were exposed to ME successively for a total of 9 days in the morning with 24 h interval in between each day of exposure. Non-attraction of males to ME was defined as absence of attraction in at least two successive exposures. Two separate lines of NR males from those locations were established. Second, the phenotypic expression of non-ME-responsiveness was ascertained by assessing lure response and mating competitiveness of NR males. Two NR lines were then reared for another 10 generations and assayed at each generation for ME attraction. In those assays, there was a gradual decrease in non-responders from ca. 35% to only 10% after the 7th generation. As pure isolines of non-ME-responding males were not attained, instead non-responders of those two lines in the 10th generation were used as sires to initiate the two reduced-ME-responding lines. Further when NR flies were evaluated for their mating competitiveness, there was no significant difference of the number of copulations between NR and control males. Third, attraction of NR B. dorsalis males to semiochemicals revealed that those males demonstrated non-significant attraction to BCP and ZN compared with higher and significant attraction with control males. Fourth, the effects of semiochemical consumption by NR males and non-ME-fed males on their mating success was further evaluated. Wind tunnel and cage bioassays results demonstrated that NR males fed on BCP or ZN was more attractive to, and copulated earlier with virgin conspecific females compared with control unfed males. Semi-natural field cage studies also showed significantly higher copulation of BCP-fed NR males compared to BCP-deprived males whilst no significant difference was observed when ZN was offered to those males. These findings suggest that in the absence of pure non-ME-responding lines of B. dorsalis, BCP and ZN are potential semiochemical compounds that can be used to improve the mating performance of sterile reduced-ME-responding males in SIT trials.